Three new species of Bidessodes Régimbart (Insecta, Coleoptera, Dytiscidae) from the Amazon river floodplain - Braga, Rafael Benzi; Ferreira-Jr., Nelson (Zootaxa, 2009)
Three new species of Bidessodes (Coleoptera, Dytiscidae) are described and illustrated from the Amazon river floodplain (“várzea”): B. nessimiani sp. nov., B. hamadae sp. nov., and B. demarcoi sp. nov. Bidessodes evanidus Young is recorded for the first time from Amazonas and Pará states, Brazil. All species are included in the subgenus Bidessodes s. str. An identification key of Bidessodes s. str. species, modified from Young (1986), is provided.